Comprehensive Sexuality Education Improves Primary Students' Explicit and Implicit Attitudes Toward Homosexuality. Issue 3 (3rd July 2022) - Hong, Li; He, Xiangyu; Xue, Lian; Guo, Lingfeng; Liu, Wenli
Abstract: Comprehensive sexuality education (CSE) is a curriculum-based process that is inclusive to gender and sexual orientation. We used the attitude toward homosexuality scale and the single category implicit association test (SC-IAT) to measure differences between explicit and implicit attitudes toward homosexuality between migrant children with 6 years CSE learning experience (experimental group, N  = 70) and those without (control group, N  = 80). We found that the experimental group had more positive explicit and implicit attitudes toward homosexuality than the control group. In conclusion, CSE is a useful process for improving the explicit and implicit attitudes of migrant children toward homosexuality.